TEMPAT PENYIMPAN DOKUMEN BERBASIS BOT TELEGRAM - Windarti, Ayu; Ananda Sapitri, Anjelalica; Saputra, Zanu; Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Document storage often uses paper or plastic folders that are less secure, so a better security system is needed. This research designed a document security system using RFID sensors and Telegram notifications. The system uses the E-KTP as a tag to open the doorlock solenoid, with the NodeMCU ESP8266 as a means of communication to Telegram. A notification will be sent if there is a forced access attempt. If the E-KTP is compliant, the door will open and the green indicator will light up, if it is not appropriate, access will be denied, the red indicator will light up, and a notification will be sent to Telegram. The results of the study show that the system works well for Internet of Things-based monitoring with a distance of 3cm between RFID Reader and ± card. The Internet Of Things-based monitoring process on Telegram bots equipped with notifications through smartphones is running well.